One-year study of polycyclic aromatic compounds at an urban site in Grenoble (France): Seasonal variations, gas/particle partitioning and cancer risk estimation - Tomaz, Sophie; Shahpoury, Pourya; Jaffrezo, Jean-Luc; Lammel, Gerhard; Perraudin, Emilie; Villenave, Eric; Albinet, Alexandre (The Science of the total environment, 2016)
21 PAHs, 27 oxy-PAHs and 32 nitro-PAHs were measured every third day over a year in both gaseous (G) and particulate PM10 (P) phases in ambient air of Grenoble (France). Mean total concentrations (G+P) of PAHs and oxy-PAHs were in the same range and about 10ngm(-3). Nitro-PAHs were 50 to 100 times less concentrated averaging 100pgm(-3). Polycyclic aromatic compound (PAC) concentrations were 5 to 7 times higher in "cold" period (October to March) than in "warm" period (April to September). Seasonal variations may be explained by higher primary emissions from residential heating, especially biomass burning in "cold" season. Meteorological conditions and influence of the geomorphology around Grenoble, with the formation of thermal inversion layers leading to the stagnation of pollutants, were additional key parameters. Maximum individual PAC concentrations were observed during two PM10 pollution events in December and February-March. Chemical processes and secondary formation of oxy- and nitro-PAH were probably enhanced by the accumulation of the pollutants during these events. PAC gas/particle partitioning depended on compound molecular weight and vapour pressure. Gas/particle partitioning of oxy- and nitro-PAHs were evaluated using a multi-phase poly-parameter linear free energy relationship model. The PAC cancer risk was assessed using toxic equivalency factors available in the literature (19 PAHs, 10 nitro-PAHs and 1 oxy-PAH). Overall, particle-bound PACs contributed about 76% of the cancer risk. While PAHs accounted for most of the total PAC cancer risk, oxy- and nitro-PAHs could account for up to 24%. The risk quantification across substance classes is limited by toxicological data availability.
Keywords: polycyklické aromatické uhlovodíky; pevné částice; Gases; Risk; NPAH; Aerosol; riziko; Gas/particle partitioning model; Environmental Monitoring; Air quality; Polycyclic Aromatic Hydrocarbons; PAH; Air Pollutants; OPAH; Particulate Matter; Francie; France; látky znečišťující vzduch; plyny; monitorování životního prostředí; Cities; roční období; Seasons; Neoplasms; nádory; velkoměsta